Do as i say not as i did : gaining wisdom in business through the mistakes of highly successful people - Frank, Carol (Brown Books Publishing, 2005)
This modern take on "Aesop for the Entrepreneur" shares candid and poignant stories of overcoming adversity from thirty of today's business leaders in a highly personal, insightful, and entertaining format. There are many inspirational books about successful ventures, but this book features brave business leaders baring their souls about how they got hit, and lived to tell the tale. The sometimes painful, often incredible details will have readers shaking their heads in disbelief, often in thanks that it wasn't them. Our human instinct is to pay closer attention to lessons learned from the mistakes of others -- in part because of our car-wreck mentality and "People Magazine" fascination with the lives of others -- but in part because we know that mistakes are the first steps toward wisdom. Realizing that some "business demigods" can make the same mistakes and face the same setbacks as the rest of us helps us understand that our own entrepreneurial dreams are not out of reach.